2009
DOI: 10.1016/s1607-551x(09)70073-7
|View full text |Cite
|
Sign up to set email alerts
|

The First Attempt at Initiating Problem‐Based Learning as A Method of Teaching–Learning at the University of Medical Sciences in Poznan, Poland

Abstract: The main objective of problem-based learning (PBL) is to provoke students to solve a new problem by themselves. The aim of this study was to investigate whether PBL was a better method of teaching basic and advanced life support to medical students compared with the classical method. The research was undertaken in 2002 in accordance with the European Guidelines 2000 and involved 36 medical students in year 4. The students were divided into two groups: experimental PBL group (17 students) and the control-classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
1
8
1
2
Order By: Relevance
“…The results of these studies have found PBL to be better[13141516] or comparable[217] to the traditional lecture-based method in terms of the improvement in the cognitive skills. PBL may not dramatically affect the knowledge scores but may significantly improve the knowledge retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies have found PBL to be better[13141516] or comparable[217] to the traditional lecture-based method in terms of the improvement in the cognitive skills. PBL may not dramatically affect the knowledge scores but may significantly improve the knowledge retention.…”
Section: Discussionmentioning
confidence: 99%
“…[17] PBL is reported to be a better method of teaching BLS and ACLS to undergraduate medical students than the classical lecture-based method. [15] A previous randomised prospective trial, comparing two methods of teaching BLS/ACLS, i.e., lecture-based multimedia presentation and case-based discussions found that both methods equally improve the level of cognitive skills among medical students. [2] The major limitation with most of the aforementioned studies is a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Out of these nine studies, four and five were performed in undergraduate and postgraduate anesthesia teaching, respectively. Amongst the four articles in undergraduate teaching, three assessed the student satisfaction with PBL in comparison to traditional lecture-based method [1, 8, 9], and one assessed the educational objectives accomplished with PBL [10]. The relevant clinical studies in postgraduate teaching compared PBL with traditional lecture-based method only in specific topics in anesthesiology like ethical aspects [11], preanesthetic assessment [12], intensive care [13], and continued medical education on air embolism [14].…”
Section: Literature Searchmentioning
confidence: 99%
“…Grzeskowiak et al [8] concluded that PBL is a better method of teaching basic life support (BLS) and advanced cardiac life support (ACLS) to undergraduate medical students than the classical lecture-based method. The assessment method used was multiple-choice question and clinical skill testing before and after the session.…”
Section: Pbl Research In Anesthesiamentioning
confidence: 99%
See 1 more Smart Citation